2022
DOI: 10.3390/nu14183745
|View full text |Cite
|
Sign up to set email alerts
|

The Lactobacillus gasseri G098 Strain Mitigates Symptoms of DSS-Induced Inflammatory Bowel Disease in Mice

Abstract: Inflammatory bowel disease (IBD) is a recurring inflammatory disease of the gastrointestinal tract with unclear etiology, but it is thought to be related to factors like immune abnormalities and gut microbial dysbiosis. Probiotics can regulate host immunity and gut microbiota; thus, we investigated the alleviation effect and mechanism of the strain Lactobacillus gasseri G098 (G098) on dextran sodium sulfate (DSS)-induced colitis in mice. Three groups of mice (n = 8 per group) were included: normal control (NC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Ulcerative colitis (UC) is one subtype of inflammatory bowel disease (IBD) that has a high incidence and prevalence in the worldwide ( Lima et al., 2021 ). It is also thought to be intricately caused by variable factors, including genetic ( Hedin et al., 2015 ), immunological and environmental aspects ( Braun and Wei, 2007 ), of which the gut microbiota dysbiosis may play important roles ( Sheehan et al., 2015 ; Kump et al., 2018 ; Zhang et al., 2022 ). Despite available therapies, including corticosteroids, anti-tumor necrosis factor alpha (TNF-α) agents, aminosalicylates, immunomodulators, and surgery ( Weisshof et al., 2018 ), development of new therapies and investigation of alternative strategies are in urgent need for amount of patients who are unresponsive to these existing treatments or present secondary failure during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis (UC) is one subtype of inflammatory bowel disease (IBD) that has a high incidence and prevalence in the worldwide ( Lima et al., 2021 ). It is also thought to be intricately caused by variable factors, including genetic ( Hedin et al., 2015 ), immunological and environmental aspects ( Braun and Wei, 2007 ), of which the gut microbiota dysbiosis may play important roles ( Sheehan et al., 2015 ; Kump et al., 2018 ; Zhang et al., 2022 ). Despite available therapies, including corticosteroids, anti-tumor necrosis factor alpha (TNF-α) agents, aminosalicylates, immunomodulators, and surgery ( Weisshof et al., 2018 ), development of new therapies and investigation of alternative strategies are in urgent need for amount of patients who are unresponsive to these existing treatments or present secondary failure during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that the following three criteria must be met for independent genetic variants as IVs in MR studies 18 : (1) IVs are closely related to exposure; (2) There is no pleiotropic association between IVs and any potential confounders; (3) IVs have no direct effect on the outcome except affecting the outcome by associated exposure (Figure 1). The latter two criteria are unrelated to pleiotropy.…”
Section: Selection and Validation Of Instrumental Variablesmentioning
confidence: 99%
“…F-statistics are commonly used to assess the strength of the correlation between instrumental variables and exposure. The equation of F-statistic is 2 represents the exposure variance interpreted by the selected SNPs, n is the number of samples, and k is the number of IVs included. An F value less than 10 indicated a weak correlation between the included IV and exposure, and this IV was removed.…”
Section: Selection and Validation Of Instrumental Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory bowel disease was highly related to disturbed gut microbiota, while probiotics can mitigate colitis through modulating host immunity and the gut microbiome [ 10 ]. Clinical symptoms gained considerable improvement after probiotics administration, accompanied by a healthier change of serum cytokines, including a significant decrease of serum pro-inflammatory factors, Interleukin-6 (IL-6), Interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), and a sharp increase of the serum anti-inflammatory factor Interleukin-13 (IL-13) [ 11 ]. Evidence showed that Paeonol restricted the development of atherosclerosis with respect to the restoration of the balance of Treg/Th17, which indirectly downregulated the protein expression of LOX and fibrosis-related indicators (MMP-2/9 and collagen I/III).…”
Section: Introductionmentioning
confidence: 99%